Risk factors for serious adverse events due to cytotoxic chemotherapy for advanced non-small cell lung cancer. (2016) - Suina, Kentaro; Shukuya, Takehito; Koyama, Ryo; Asao, Tetsuhiko; Honma, Yuichiro; Kato, Motoyasu; Muraki, Keiko; Shibayama, Rina; Shimada, Naoko; Takahashi, Fumiyuki; Sakuraba, Shoko; Takahashi, Kazuhisa
Abstract: Background: Chemotherapy is a standard treatment for patients with advanced non-small cell lung cancer (NSCLC); however, it occasionally causes adverse events. Serious adverse events (SAEs) are defined as any untoward medical occurrence that is related to drug use and results in life-threatening experiences, prolonged or initial hospitalization, or significant or persistent disability. However, as few studies have reported on the risk factors for SAEs, we aimed to identify the factors that could predict SAEs in NSCLC. Patients and methods: We retrospectively reviewed the medical records of patients treated with pemetrexed plus cisplatin (PC), paclitaxel plus carboplatin plus bevacizumab (BVCP), docetaxel monotherapy (DTX), or pemetrexed monotherapy (PEM) at Juntendo University Hospital between January 2010 and March 2012. Two investigators reviewed the clinical records and judged SAEs. Multivariate analyses were performed to identify independent risk factors for SAEs among the following factors: gender, age, performance status, line of chemotherapy, preexisting interstitial lung disease (ILD), smoking status, and chemotherapeutic regimen. Results: A total of 252 patients received chemotherapy (male/female, 162/90; median age [range], 66 years [36–92 years]; stage III/stage IV/postoperative recurrence, 53/145/54; adenocarcinoma/squamous cell carcinoma/not otherwise specified, 211/24/17; PC/BVCP/PEM/DTX, 50/ 51/ 67/ 84). Of these, 30 (11.9%) patients experienced SAEs. The SAEs were anorexia/nausea in 10 patients, febrile neutropenia (FN) in eight, drug-induced ILD in six, infection (sepsis, pleural infection, soft tissue infection) in three, elevated creatinine level in one, pneumothorax in one, and gastric hemorrhage in one. Treatment-related death was noted in four patients, two with drug-induced ILD, one with FN, and one with infection. Multivariate analysis revealed that preexisting ILD (odds ratio=5.06; p =0.0012) and the chemotherapeutic regimen ( p =0.00-0.03) were significantly associated with SAEs. Conclusions: Preexisting ILD and the chemotherapeutic regimen were risk factors for the prediction of SAEs in the treatment of NSCLC in clinical practice.